2018
DOI: 10.1063/1.5025510
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of RF antennas to large volume helicon plasma

Abstract: Large volume helicon plasma sources are of particular interest for large scale semiconductor processing, high power plasma propulsion and recently plasmamaterial interaction under fusion conditions. This work is devoted to studying the coupling of four typical RF antennas to helicon plasma with infinite length and diameter of 0.5 m, and exploring its frequency dependence in the range of 13.56 − 70 MHz for coupling optimization. It is found that loop antenna is more efficient than half helix, Boswell and Nagoya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
3
5
0
Order By: Relevance
“…This is consistent with the experimental observation that the discharge transits from blue-colour mode to blue-core mode [9]. The decreased power for shrunk density profiles implies that certain magnitude of plasma density near edge is beneficial for power coupling, which also agrees with previous studies [40,41,42,43,44]. More interestingly, we find that the power deposition is hollow in radius for all field strengths and its peak moves closer to axis when the field strength increases.…”
Section: Power Depositionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the experimental observation that the discharge transits from blue-colour mode to blue-core mode [9]. The decreased power for shrunk density profiles implies that certain magnitude of plasma density near edge is beneficial for power coupling, which also agrees with previous studies [40,41,42,43,44]. More interestingly, we find that the power deposition is hollow in radius for all field strengths and its peak moves closer to axis when the field strength increases.…”
Section: Power Depositionsupporting
confidence: 92%
“…This could be attributed to the plasma density near edge which is too low to efficiently couple the power from antenna into core. This critical role of edge density has been also claimed by other studies [40,41,42,43,44].…”
Section: Step-like Function Theorysupporting
confidence: 81%
“…It is commented that (a-c) are generic phenomena for plasma discharge and insufficient to support the remarkable ionisation rate and high density of helicon sources, and more attention should be paid to (d-e) which involves the critical parameter of confining magnetic field that promotes the density jump from inductively coupled plasma to helicon mode; further, (4) and ( 5) rely on density magnitude and density gradient, respectively, and optimum discharge may be achieved when the required density magnitude comes across with the largest density gradient at the same location. Then, the sign (positive or negative) and zero-crossing position of second-order density gradient are shown to effect the power absorption profile significantly, consistent with (5) [32][33][34]. Moreover, it is suggested that the power deposition profile could be shaped by designing the antenna of particular geometry to excite the required axial current distribution, considering their resemblance.…”
Section: Introductionsupporting
confidence: 54%
“…Therefore, for n e0 = 1 × 10 13 cm −3 in this study, parabolic distribution is better than Gaussian distribution in terms of power deposition effect. [15] Because of these, this article mainly takes the parabolic distribution as the research object.…”
Section: Numerical Simulation Analysismentioning
confidence: 99%
“…In this regard, this article has launched a study on the effect of magnetic field on the power deposition based on HMHX. [13] HELIC code is frequently used in the design of RF plasma sources, [14,15] Compared with other codes (such as ANTENA2 code, [16] SPIREs code, [17] ANAMANT code [18] ), HELIC code calculates the energy deposition of H wave and TG wave and the distribution of electric field, magnetic field and current through electromagnetic field theory analysis. This code uses specific boundary conditions to solve 6 radially coupled differential equations to obtain two independent waves (H wave and TG wave).…”
Section: Introductionmentioning
confidence: 99%